Exploring carbon emission drivers in G5 economies: the interplay of green technology, environmental performance, energy intensity, and economic growth - Hao, Qingdong; Arshad, Rimsha (Frontiers in Environmental Science, 2025)
This study investigates the impact of green technology (GT), energy intensity (EIN), environmental performance (EPR), and economic growth (GDP) on carbon emissions (CEM) across the G5 economies—Brazil, China, India, Mexico, and South Africa—over the period 2000 to 2022. Unlike previous studies, this research integrates these four variables in a unified framework using Method of Moments Quantile Regression (MMQR) and panel Granger causality tests—an approach rarely applied to emerging economies collectively. This allows for a deeper, distribution-sensitive understanding of how technological, economic, and environmental factors interact to shape emissions trajectories across high- and low-emission contexts. Employing MMQR, we assess the heterogeneous effects of these drivers across the carbon emission distribution, with particular attention to the potential decoupling of economic growth from environmental degradation. To further explore directional dynamics, the Dumitrescu and Hurlin panel Granger non-causality test is applied. The empirical results reveal that green technology development and economic growth are significantly associated with reductions in carbon emissions, especially in higher emission quantiles, indicating that environmentally sustainable growth is attainable through targeted technological investments. In contrast, both energy intensity and environmental performance indicators show a positive association with emissions, suggesting that increased energy demand and limited effectiveness of current environmental measures hinder mitigation efforts. Causality analysis confirms that both GT and GDP Granger-cause carbon emissions, whereas EIN and EPR do not exhibit statistically significant causal relationships. These findings underscore the pivotal role of green technology in advancing low-carbon transitions and support the design of integrated policy frameworks aimed at enhancing energy efficiency, fostering innovation, and aligning with Sustainable Development Goals (SDGs), particularly those related to climate action and sustainable urban development. The study provides actionable insights for policymakers in the G5 and other emerging economies striving to balance economic growth with environmental sustainability.